2015
DOI: 10.5604/15093492.1143539
|View full text |Cite
|
Sign up to set email alerts
|

Hallux Checkrein Deformity Resulting from the Scarring of Long Flexor Muscle Belly - Case Report

Abstract: A case of posttraumatic checkrein deformity of the hallux is presented. This deformity is most often caused by scarring of the muscle belly or tethering of the tendon. A 22-year old woman developed a hallux checkrein deformity after a bimaleolar fracture. Intraoperatively, a linear scar tethering the muscle belly to the posterior tibia was observed. Resection of the scar allowed for full flexor hallucis longus mobility. Full hallux range of motion as well as foot function was restored. The cause of the checkre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(20 reference statements)
0
1
0
1
Order By: Relevance
“…It has been suggested that the deformity is a consequence of (1) entrapment of the FHL between calli at the fracture site, 15) (2) tethering of the FHL within the scar tissue, 16) (3) scarring at the musculotendinous junction, 17) and (4) fibrotic contracture after subclinical compartment syndrome. 9) However, it can be difficult to identify the exact cause of the deformity in each case.…”
Section: Etiologymentioning
confidence: 99%
“…It has been suggested that the deformity is a consequence of (1) entrapment of the FHL between calli at the fracture site, 15) (2) tethering of the FHL within the scar tissue, 16) (3) scarring at the musculotendinous junction, 17) and (4) fibrotic contracture after subclinical compartment syndrome. 9) However, it can be difficult to identify the exact cause of the deformity in each case.…”
Section: Etiologymentioning
confidence: 99%
“…Etiyolojisinde i) FHL'nin tibia, kalkaneus ya da talus kırıkları sonrası gelişen kaynama (kallus) dokusu içerisinde hapsolması, ii) FHL'nin nedbe dokusu içerisinde hapsolması, iii) derin kompartmanında gelişen kompartman sendromu nedeniyle kas gövdesindeki nedbe dokusu nedeniyle kasın kı-salması ve iv) yaralanmayı takiben muskulotendinoz bölgede kas ile tibia arasında gelişen yapışıklıklar yer almaktadır. [15][16][17] Tedaviye yönelik ilk adım, FHL'nin durumunu netleştirmek amacıyla ultrasonografi ve manyetik rezonans görüntülemeleri elde edilmesidir. Nedene yöne-lik yapışıklıkların cerrahi olarak giderilmesi, tendonun Z-plasti ile uzatılması ya da fleksör tenotomiye ek olarak başparmak interfalangeal artrodez yöntemi tanımlanmıştır.…”
Section: Checkrein Deformitesiunclassified